Bearing Capacity Studies on Square Steel Tube Confined Steel Reinforced Concrete Column under Eccentric Load - Tongfeng Zhao (Advances in Civil Engineering)
In the present study, an experimental research was conducted on square steel tube confined steel reinforced concrete column under eccentric load. The major parameters of the specimens included slenderness ratio, eccentricity ratio, and structural steel reinforced ratio. According to the tested results, the eccentricity ratio, from 0 to 0.55, significantly affects the structural bearing capacity. The slenderness ratio, from 3 to 8, and steel reinforced ratio, from 0.3 to 0.41, slightly affect the capacity. Furthermore, a numerical analysis program was developed, and the calculated results are well consistent with the experimental results. Also, the theoretical formula for eccentrically loaded columns was proposed based on numerical results.